Pengaruh Inklusi Keuangan, Persepsi Risiko dan Persepsi Persepsi Kemudahan terhadap Konsumen Pinjaman Online - Azmi, Nurul; Widiyasti, Baiq Dinna; Zahrah, Zahrah; Hendri, Wira; Dethan, Stevany Hanalyna (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The rapid growth of online loan platforms has transformed access to credit, especially for individuals who face barriers to traditional financial services. In Lombok Island, West Nusa Tenggara, Indonesia, honorary teachers often experience limited access to formal financing and have relatively low incomes, making them particularly vulnerable to financial risks and overindebtedness due to the increasing use of online loans. This study aims to empirically investigate how financial inclusion, risk perception, and perceived ease of use influence the behavior of online loan consumers, focusing specifically on this group of teachers. Using a quantitative research approach, data were collected from 100 honorary teachers through a structured survey. The instruments used in the study underwent validity and reliability testing, confirming their accuracy and consistency for the research context. The results of multiple linear regression analysis indicate that financial inclusion, risk perception, and perceived ease of use simultaneously and individually exert a positive and significant impact on the online loan consumption behavior of teachers. Notably, perceived ease of use emerged as the most influential factor, suggesting that the simplicity and convenience of accessing fintech lending platforms play a crucial role in driving adoption among this vulnerable population. These findings provide important insights for policymakers and financial educators to develop targeted financial literacy programs and inclusive fintech services. By emphasizing ease of use while addressing risk awareness and financial accessibility, stakeholders can better protect honorary teachers and similar vulnerable groups from the potential pitfalls associated with online loans, fostering safer and more responsible financial behavior.